Dispositional Beliefs and Opportunity Beliefs as Cognitive Competence Mediated by Entrepreneurial Mindset towards Entrepreneurial Behavior - Istanto, Alleta Antjani; Indudewi, Febe Yuanita Ratna (Jurnal Entrepreneur dan Entrepreneurship, 2024)
The aim of this study is to investigate the impact of cognitive competency, which includes dispositional and opportunity beliefs, on entrepreneurial behavior, as mediated by an entrepreneurial mentality. Gender is used as a control variable. This study utilizes a quantitative approach and examines data from alumni of XL Axiata’s CSR program, XL Future Leaders (XLFL) Batch 6-10. Data is collected via an online questionnaire and analyzed using PLS-SEM. The results suggest that dispositional beliefs and opportunity beliefs directly influence entrepreneurial mindset, which positively impacts entrepreneurial behavior. The significance of the relationship between the variables also affected by the gender. When gender is added as a control variable, the association between dispositional belief and entrepreneurial behavior becomes insignificant. This research also explains further on individual cognitive competence that is shaped through family background. The research contributes to the understanding of the complex interplay between cognitive competence, entrepreneurial mindset, and entrepreneurial behavior. Future research possibilities include investigating the moderation effect of gender and using longitudinal designs to acquire a more detailed understanding of these interactions.